1996
DOI: 10.1183/09031936.96.09112340
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between breathlessness and hypoxic and hypercapnic ventilatory response in patients with COPD

Abstract: R Re el la at ti io on ns sh hi ip p b be et tw we ee en n b br re ea at th hl le es ss sn ne es ss s a an nd d h hy yp po ox xi ic c a an nd d h hy yp pe er rc ca ap p--SThe mean value of the breathlessness at two different levels of ventilation was greater during HVR than during HCVR, suggesting that hypoxia is dyspnogenic independently of ventilatory stimulation. The HCVR was inversely correlated with the breathlessness response to ventilation, while similar correlation was partly present for HVR. The HVR w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Our results confirm this theory. In contrast, Kobayashi et al 31 found that hypercapnia had no additional dyspnogenic effect during a hypercapnic ventilatory response which was also seen by Clague et al 32 Interestingly, Kobayashi et al also found a dyspnogenic effect of hypoxia during a hypoxic ventilatory response which occurred during moderate hypoxia (desaturation to 80%). Peripheral chemoreceptors normally respond to hypoxia only at very low levels of Pa o 2 ; the relationship between afferent impulse activity and Pa o 2 is hyperbolic.…”
Section: Discussionmentioning
confidence: 89%
“…Our results confirm this theory. In contrast, Kobayashi et al 31 found that hypercapnia had no additional dyspnogenic effect during a hypercapnic ventilatory response which was also seen by Clague et al 32 Interestingly, Kobayashi et al also found a dyspnogenic effect of hypoxia during a hypoxic ventilatory response which occurred during moderate hypoxia (desaturation to 80%). Peripheral chemoreceptors normally respond to hypoxia only at very low levels of Pa o 2 ; the relationship between afferent impulse activity and Pa o 2 is hyperbolic.…”
Section: Discussionmentioning
confidence: 89%
“…Carbon dioxide retention is more strongly correlated with breathlessness in lung disease than is hypoxemia. 33 In patients who can increase breathing and lower arterial partial pressure of carbon dioxide, breathlessness will be limited. 34 This is similar to what is experienced by most people on ascent to high altitude: arterial hypoxemia is present but subjective breathlessness is limited by subtle, often unnoticed increases in the respiratory rate that helps the lungs “blow off” enough arterial carbon dioxide to mitigate the sensation of dyspnea.…”
Section: Hypoxemia and Breathlessness: Variability In Humansmentioning
confidence: 99%
“…Low self-efficacy, anxiety, depression, hypoxia, hypercapnia, hypoxia-induced cognitive decline, skeletal dysfunction, weight loss or obesity and other concomitant diseases each compromise patients' breathing abilities and functional level in daily living (American Thoracic Society/European Respiratory Society, 1999; Davis et al, 2006;Kobayashi et al, 1996;Masuda et al 2001;Nonoyama et al, 2007). Consequently, coping with breathlessness may constitute a complex process involving physiological, cognitive, affective and psychosocial dimensions (Nici et al, 2006).…”
Section: Introductionmentioning
confidence: 99%